Gambaran Kejadian Kurang Gizi pada Ibu Hamil di Rumah Sakit Umum Daerah Kefamenanu Kabupaten Timur Tengah Utara Provinsi Nusa Tenggara Timur: Overview of the Incidence of Maternal Undernutrition among Pregnant Women at Kefamenanu Regional General Hospital, North Central Timor Regency, East Nusa Tenggara Province - Zulhaedah Zulhaedah; Indrawahyuni Mardi; Kasmawati Kasmawati (Indonesia Berdaya, 2026)
Adequate nutrition is essential for human growth, development, and overall well-being. Measures to reduce the burden of disease are relatively simple and well established, including maintaining a healthy body weight, consuming a balanced and nutrient-rich diet, avoiding smoking, and engaging in regular physical activity. However, survey data from the American Dietetic Association (ADA) indicate that although many women recognize the relationship between diet and health, only one-third actually implement dietary strategies to reduce the risk of nutrition-related chronic diseases. This study aimed to describe the incidence of maternal undernutrition among pregnant women at Kefamenanu Regional General Hospital, North Central Timor Regency, East Nusa Tenggara Province, Indonesia, in 2026. This descriptive study used secondary data obtained from medical records at Kefamenanu Regional General Hospital. The data were presented in frequency distribution tables and analyzed using descriptive percentage analysis based on maternal body weight, LILA (upper arm circumference), and hemoglobin (Hb) levels. The study population consisted of 84 pregnant women, with a sample of 46 women. Overall, 39 respondents (84.78%) had good nutritional status, while 7 respondents (15.22%) were classified as undernourished. Based on body weight, 40 respondents (86.95%) had normal body weight, whereas 6 respondents (13.05%) had low body weight. Based on LILA, 10 respondents (21.74%) were classified as high risk, while 36 respondents (78.26%) were classified as low risk. Based on maternal Hb levels, 12 respondents (26.03%) were categorized as high risk, whereas 34 respondents (73.97%) were categorized as low risk. These findings indicate that although most pregnant women had good nutritional status, a considerable proportion remained at nutritional risk based on LILA and Hb levels, highlighting the importance of continuous nutritional monitoring during pregnancy. Abstrak. Nutrisi yang tepat sangat penting bagi pertumbuhan, perkembangan dan kesejahteraan manusia. Tindakan untuk mengurangi beban penyakit cukup sederhana dan telah diteliti dengan baik, yaitu mempertahankan berat badan yang sehat, makan yang seimbang, diet kaya nutrisi, tidak merokok dan olahraga teratur. Namun data survei dari American Dietetic Association (ADA) menunjukkan bahwa walaupun wanita tampak mengenali hubungan antara diet dan kesehatan, hanya sepertiganya yang benar-benar mengimplementasikan strategi diet untuk mengurangi risiko penyakit kronis yang berhubungan dengan nutrisi. Penelitian ini bertujuan untuk mengetahui Gambaran Kejadian Kurang Gizi Pada Ibu Hamil di Rumah Sakit Umum Daerah Kefamenanu Kabupaten Tengah Utara Provinsi Nusa Tenggara Timur (NTT) Tahun 2026. Dengan jenis penelitian adalah deskriptif. Data yang digunakan yaitu data sekunder yang diperoleh dari hasil pengambilan data di pencatatan rekam medik di Rumah Sakit Umum Daerah Kefamenanu Kabupaten Tengah Utara, NTT yang kemudian disajikan dalam tabel distribusi frekuensi dan dianalisis dengan formulasi presentatif berdasarkan variabel berat badan, LILA, dan kadar HB ibu. Dengan populasi yang digunakan adalah sebanyak 84 ibu dengan jumlah sampel sebanyak 46 ibu. Secara keseluruhan total sampel sebanyak 46 ibu termasuk dalam kategori status gizi baik sebanyak 39 ibu atau (84,78%), gizi kurang sebanyak 7 ibu atau (15,22%), berdasarkan kategori berat badan ibu termasuk dalam kategori baik sebanyak 40 ibu atau (86,95%), kategori kurang sebanyak 6 ibu atau (13,05%). Berdasarkan kategori LILA ibu termasuk dalam risiko tinggi sebanyak 10 ibu atau (21,74%) dan risiko rendah sebanyak 36 ibu atau (78,26%). Berdasarkan Kadar HB ibu termasuk dalam kategori risiko tinggi sebanyak 12 ibu atau (26,03%), dan risiko kurang sebanyak 34 ibu atau (73,97%).